Controlling ZIF-8 nano- and microcrystal formation and reactivity through zinc salt variations - Schejn, Aleksandra; Balan, Lavinia; Falk, Véronique; Aranda, Lionel; Medjahdi, Ghouti; Schneider, Raphaël (CrystEngComm, 2014)
We report here a simple method for controlling the crystal size and morphology of zeolitic imidazolate framework-8 (ZIF-8) nanocrystals in methanol solution. ZIF-8 crystals were prepared by mixing 2-methylimidazole (Hmim) with various zinc salts for 1 h and using a Hmim/Zn(+2) salt molar ratio of 8/1. All products prepared were assigned to a sodalite-type structure and both particle size and morphology were found to be dependent on the reactivity of the Zn(+2) salt. Small ZIF-8 crystals with diameters varying between ca. 50 and 200 nm were obtained with reactive zinc salts like Zn(acac) 2 , Zn(NO 3 ) 2 , ZnSO 4 or Zn(ClO 4 ) 2 as demonstrated by SEM, TEM and DLS analyses. The use of ZnCl 2 , Zn(OAc) 2 or ZnI 2 afforded crystals with sizes varying between ca. 350 and 650 nm. Finally, the low reactive ZnBr 2 salt was found to generate microsized crystals. Taking ZIF-8 crystals prepared from Zn(NO 3 ) 2 , Zn(OAc) 2 and ZnBr 2 as representatives and through thermogravimetric analysis and BET measurements, we also demonstrated that changes in particle size induced changes in stability and adsorption properties. The small sized ZIF-8 crystals produced from Zn(NO 3 ) 2 were found to exhibit the highest surface area (1700 m 2 g −1 ) and the best catalytic activity in Knoevenagel and Friedländer reactions.